Real‐time pricing in smart community with constraint from the perspective of advertising game. (20th June 2019) - Dai, Yeming; Li, Lu; Zhao, Pei; Duan, Jinpeng
Summary: The advertising differential game is introduced to depict the competition among electricity retailers in continuous time. A Stackelberg game model with one leader and multiple followers is established to study the real‐time pricing scheme in a smart community. By solving the optimization problem on users' side with budget constraint and the noncooperative differential game among retailers, the Stackelberg equilibrium between the retailers and the users is obtained. Finally, numerical simulation is carried out to discuss the influence of different factors on the payoff of electricity retailers and users and verify the rationality of the pricing scheme.